Gamification Approach towards Engineering Students' Engagement in Online Learning - Lee Chin, Kho; Sze Song, Ngu; Annie, Joseph; Dyg Azra, Awang Mat; Liang Yew, Ng; Ji Liang, Hau (International Journal of Information and Education Technology, 2022)
Many engineering students might encounter difficulties understanding certain topics of related courses. They feel frustrated when the teaching method is dull, and the teaching materials are not attractive. All these may lead to the demotivation of the students toward the courses. Fortunately, there are tons of teaching techniques that are introduced to help in boosting students' engagement in the classroom, such as inquiry-based learning, project-based learning, service-based learning, and others. These techniques require the student's engagement, which eventually improves students' concentration while motivating them to practice critical thinking skills. It may promote positive learning experiences. However, engineering courses comprised of various complicated theories, calculations, projects, and assignments, which may burden some students. Furthermore, in addition to the COVID 19 pandemic, the students only attend their classes online, making the learning process even more independent and challenging. Therefore, this study aims to explore the gamification approach for engineering students to increase their engagement while learning online. A batch of 116 students from the Bachelor’s Degree of Engineering in Electrical and Electronics offered by Universiti Malaysia Sarawak (UNIMAS) are invited to participate in this study. A gamified learning model that consists of four stages is created in the online platform for the second-year KNR2443 Electrical Engineering Technology (EET) course. This gamified learning model integrates students’ rank, interactive map, and video guide. A survey related to gamification is collected from the EET students who completed the gamified learning model. The results are generally positive and indicate the gamification approach can potentially improve the engineering students’ engagement and enjoyment in the learning process.